(untitled) (Jurnal Ilmiah PLATAX, 2015)
Scylla serrata is one of the dominant muddy crabs caught in Mantehage Island coastal waters, North Sulawesi. The study was aim to determine the temporal distribution of S. serrata condition i based on carapace length - weight relationship and its condition factors. Data carapace width and weight of muddy crabs collected by enumerators from Oktober 2014 to April 2015. The results showed that b value of male (2.219 â€“ 2.835) and female (1.264-2.352) were significantly different (P<0.05). Male and female crabs have a negative allometric growth pattern with b value of males tend to be larger than females. Range of values for K and Kn male crabs longer than females that male crabs tend to be fatter. Temporal distribution of this mangrove crab condition factors is assumed to be related with the reproductive cycle. The value is increasing since October to a peak season in January which estimated related to a peak of the muddy crabs spawning season in Mantehage Island coastal waters. Â Key words: growth potential, Mantehage Island coastal waters, Scylla serrata _____________________________________________________________________ 1Staf Pengajar Fakultas Perikanan dan Ilmu Kelautan UNSRAT A b s t r a k Â Scylla serrata merupakan salah satu jenis kepiting bakau yang dominan tertangkap di perairan Pulau Mantehage Sulawesi Utara. Penelitian ini bertujuan untuk mengetahui potensi pertumbuhan kepiting bakau ditinjau dari hubungan panjang karapas dengan berat. Data panjang karapas dan berat kepiting bakau dikumpulkan melalui nelayan setempat sebagai enumerator sejak Oktober hingga April Â 2015. Hasil menunjukkan nilai b antara kepiting jantan (2,219 â€“ 2,835) dan betina (1,264 - 2,352) berbeda nyata (P<0,05). Keduanya memiliki pola pertumbuhan allometrik negatif dengan nilai b kepiting jantan cenderung lebih besar dibandingkan betina. Kisaran nilai K dan Kn menunjukkan kepiting jantan lebih panjang dibandingkan betina sehingga kepiting jantan cenderung lebih gemuk. Sebaran faktor kondisi kepiting bakau diduga terkait dengan siklus reproduksinya. Nilai faktor kondisi meningkat sejak bulan Oktober 2014 hingga puncaknya pada bulan Januari 2015yang diduga pada saat tersebut merupakan puncak musim pemijahan kepiting bakau di perairan P. Mantehage. Kata kunci: potensi pertumbuhan, perairan P. Mantehage, Scylla serrata